Kompetensi Interpersonal Mahasiswa - Idrus, Muhammad (Unisia, 2012)
This research proposes to evaluate a correlation between same-aged friendship interaction and inter-personal competence of students. The population are all students of the Faculty of Psychology and Social and Cultural Science of the Universitas Islam Indonesia. Samples are 25 percent of the population, 315 students, taken through the stratified proportional random. Using a product moment correlation analysis of Pearson, it is revealed that the value of the correlation between the same-aged interaction and inter-personal competence is 0.457 (p=0.000). This shows a significant correlation between these variables. Keywords: same-age friendship, interpersonal competence, correlation.